Chinese olive (Canarium album Rauesch.): a critical review on its nutritional value, phytochemical composition, health benefits, and practical applications - Yu, Kuo; Wang, Yan; Hu, Wen-Jing; Zhang, Zhao-Jiong; Zhou, Guan-Yu; Sun, Shi; Kuang, Hai-Xue; Wang, Meng (Frontiers in Pharmacology, 2023)
Chinese olive is a popular fruit with a long history of cultivation and consumption. As a fruit with edible, nutritional, and even medicinal value, the Chinese olive has attracted increased interest from both nutrition researchers and health-conscious consumers. Chinese olive is a rich nutrient source, including essential and non-essential amino acids, various fatty acids, organic acids, vitamins, microelements, and high-quality dietary fibers. It is also an important natural source of phytochemicals such as phenolic acids, flavonoids, phenylpropanoids, and other bioactive compounds. The nutritional and phytochemical compounds obtained from the Chinese olive exhibit unique and potent biological activities, explaining its various benefits to human health, including anti-Helicobacter pylori, anti-influenza, antidiabetes, anti-inflammatory, anti-tumor effects, among others. This review focuses on recent studies on Chinese olives and aims to summarize the major advances in their nutritional value, phytochemical composition, health benefits, and practical applications. It provides a reference for further research on Chinese olives and their properties and the development of novel functional products.